Cascade flow rate-temperature control system design based on PID controller using direct synthesis tuning method - Pradana, Mochamad Rizky; Aristoni, Deni; Triyanto, Roni Heru; Yuliatin, Umi; Budi, Suka Handaja (Jurnal Polimesin, 2024)
Cascade control is one of the multi-loop control schemes that aim to increase the performance of closed-loop control systems. Temperature control on the outlet of a plate heat exchanger often from suffers errors in the control variable and designated set point, so it is necessary to use cascade control in order to stabilize output temperature and reduce the disturbance. The Proportional Integral Derivative (PID) controller in conjunction with the direct synthesis tuning method is used due to ease of implementation and to modify the second-order process model and become the first-order process model, simplifying the model. In cascade control, the flow rate control is designated as the secondary loop, while the temperature control functions as the primary loop. The PID controller model is designed with direct synthesis tuning on the cascade flow rate temperature control, resulting a proportional gain of 2.15%, of 1.976 s, and τd of 0 seconds on the flow rate control loop. Whereas on the temperature control loop, the proportional gain is 13.23%, is 66.3 s and the τd is 7 seconds. The transient responses from cascade flow rate temperature control from Simulink are rise time (tr) = 106.7 seconds, settling time (ts) = 183 seconds, and maximum overshoot = 0%. Based on this parameter, the controller generates Process Variable (PV) responses from master control that can reach the Set Point (SP) without overshoot, maintain a steady state, and reduce the disturbance from slave control within 20 seconds of the response increasing from the steady state condition